Arthur Schnitzler: Blumen Historisch-kritische Ausgabe - Schwentner, Isabella (Walter de Gruyter GmbH, 2017)
Historical-critical edition of Arthur Schnitzler's novella Blumen. The volume presents all bequeathed manuscripts as full-size facsimiles with transcriptions and a print text with a display of textual variants. It is completed by a commentary and describes the highly complex genesis of the text in detail.